Automated conflict detection between medical care pathways. Issue 7 (10th October 2017) - Weber, Philip; Filho, João Bosco Ferreira; Bordbar, Behzad; Lee, Mark; Litchfield, Ian; Backman, Ruth
Abstract: Clinical guidelines specify sequences of steps (care pathways) to treat patients with single conditions. Increasingly, many patients exhibit "multimorbidity, " several chronic conditions needing concurrent treatment. However, applying multiple guidelines in parallel can lead to conflicts, eg, between prescribed drugs, lifestyle intervention recommendations, or treatment schedules. In computer science, process languages used to design and reason about software development and business process management are similar to clinical pathways. Using formal model transformation, composition and analysis methods, models can be combined and conflicts detected and resolved. We propose BPMN+V, a data‐driven formal model for clinical care pathways, as an extension of Business Process Model and Notation. We describe a method for conflict detection using a transformation of BPMN+V to Coloured Petri Nets and a state‐space method for detection of conflict in composed models. We present results from a case study, showing that common conflicts are successfully detected, and propose extension to a complete framework for efficiently recommending resolutions to medical conflicts in composed care pathway models. Abstract : We present BPMN+V, a representation for modeling clinical care pathways, particularly with regard to their dependence on and interaction with data. Using this notation, we describe and evaluate a method to detect conflicts between multiple care pathways followed concurrently.